Free and Compulsory Education Bill, 2004 - Sarada Balagopalan (EPW Commentary August 7, 2004, 2004)
The new draft bill on free and compulsory education justifies the parallel system of schooling by juxtaposing the moral urgency of schooling as 'opportunity' versus unbridled toil of the child labourer. The two-tier system of schools contradicts its own high-minded endeavour of having schooling serve as a means to end child labour. Schooling becomes compulsory for fear of drawing penalty, while little attention is paid to ensuring quality education